EFFECTIVENESS OF SUBSTANTIVE TECHNICAL EDUCATION AND TRAINING FOR ISLAMIC SENIOR HIGH SCHOOL BIOLOGY TEACHERS - Saputro, Budiyono; Lestari, Budi; Widiyanti, Fenny; Saputra, Heru (Unnes Science Education Journal, 2019)
The purpose of this study was to determine the effectiveness of substantive technical education and training program for Islamic High School (Madrasah Aliyah/MA) throughout Central Java and Yogyakarta. Quantitative research with "One-Group Pretest-Postest Design" research design was used. Population and samples were taken from all Biology teachers throughout Central Java and Yogyakarta with a total of 33 participants. Instruments for data retrieval were questions about pretest and posttest. The data were in the form of participants’ pretest and posttest results. Based on the Wilcoxon test results, it obtained t count -3.083, while p = 0.002 <0.05, it could be concluded that substantive education and training can effectively improve the material mastery for Madrasah Aliyah biology teachers. The materials were the analysis of Graduate Competence Standard (SKL), Core Competence (KI), Basic Competence (KD), Biology Indicators of Madrasah Aliyah, essential material of anatomy and physiology of animals and plants, cells, animal and plant tissues, metabolic processes, biotechnology and their application, genetic in inheritance, and the practice of Madrasah aliyah biology learning.